Comparison of Intraoperative and Postoperative Bleeding Risks Between Robot-assisted and Laparoscopic Hysterectomy - Tae Yeong Kim; So Hee Park; Jae Hong Sang; Jeong In Choi; Soo-Ho Chung (IMR Press, 2024)
Background: This study aimed to compare bleeding risks between robot-assisted and laparoscopic hysterectomy and to provide a guidance for selection of surgical methods to minimize intraoperative bleeding. Methods: We enrolled patients who underwent robotic or laparoscopic hysterectomy at our institution from January 2021 to December 2022. We compared the percentage decrease in hemoglobin levels from within 1 month prior to surgery to postoperative days 1 and 3; the total Jackson-Pratt (JP) drainage by postoperative day 2 or 3; input/output (I/O) difference which means the subtraction of all output including urine and JP drainage volume from the total input of administered fluids, which implies amounts of blood lost on the day of surgery; and the numbers of patients who required transfusions. We compared patients who underwent robotic and laparoscopic hysterectomy, and subgroups thereof based on the uterine weight and the extent of adhesiolysis. Analyses employed IBM SPSS software. The independent samples t-test was used to compare the various groups. A p-value less than 0.05 was considered statistically significant. Results: Robotic hysterectomy demonstrated superior outcomes in terms of the total JP drainage compared to laparoscopic hysterectomy. However, no significant differences were demonstrated between the two surgical procedures in terms of the percentage decrease in hemoglobin levels from 1 month prior to surgery to postoperative days 1 or 3, or I/O difference on the day of surgery. Notably, only patients who received laparoscopic hysterectomy required blood transfusions. Conclusions: Our results support the hypothesis that robotic hysterectomy is not only similar, but actually superior to laparoscopic hysterectomy in terms of bleeding control. Our findings offer valuable guidance when decisions are made to choose surgical method via collaborative consultations involving a medical team and a patient. In particular, our results are beneficial for patients seeking to minimize bleeding during surgery and for those who are unfamiliar with the differences between robotic and laparoscopic hysterectomy.